2014
DOI: 10.1007/s11250-014-0717-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and impact of retained fetal membranes on performance of dairy bovines reared under subtropical conditions

Abstract: The risk factors and impact of retained fetal membranes (RFM) on productive and reproductive performance of crossbred cattle, Zebu cattle, and Murrah buffalos were evaluated using data spread over 12 years. Multivariable logistic regression model was used to identify risk factors and to quantify their odds ratio (OR). Overall incidence of RFM in crossbred cattle, Zebu cattle, and Murrah buffalos were 26, 16, and 13 %, respectively; and significant risk factors for RFM in crossbred cattle were abortion (OR = 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 8 publications
1
9
0
9
Order By: Relevance
“…Bovine and buffalo fetal membranes are expelled within 12 hr after delivery of the calf (Drillich et al, ; El‐Malky et al, ); failure to expel it within this period results in retention of fetal membranes (RFM). The reported incidence of RFM varies: Friesian cows show from 3.6% in the United Kingdom (Esslemont and Kossaibati, ) to 24.9% in Egypt (Gaafar et al, ); in Zebu cows and its crosses, and in Murrah buffalo, the incidence of RFM is 26, 16, and 13%, respectively (Kumari et al, ). RFM results in considerable economic loss due to decreased milk production (Dubuc et al, ; Kumari et al, ); longer interval to first estrus and breeding; increased number of services per conception; lower conception rate and higher incidence of metritis (LeBlanc, ; Gaafar et al, ); and increased culling rate (Beagley et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bovine and buffalo fetal membranes are expelled within 12 hr after delivery of the calf (Drillich et al, ; El‐Malky et al, ); failure to expel it within this period results in retention of fetal membranes (RFM). The reported incidence of RFM varies: Friesian cows show from 3.6% in the United Kingdom (Esslemont and Kossaibati, ) to 24.9% in Egypt (Gaafar et al, ); in Zebu cows and its crosses, and in Murrah buffalo, the incidence of RFM is 26, 16, and 13%, respectively (Kumari et al, ). RFM results in considerable economic loss due to decreased milk production (Dubuc et al, ; Kumari et al, ); longer interval to first estrus and breeding; increased number of services per conception; lower conception rate and higher incidence of metritis (LeBlanc, ; Gaafar et al, ); and increased culling rate (Beagley et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The reported incidence of RFM varies: Friesian cows show from 3.6% in the United Kingdom (Esslemont and Kossaibati, ) to 24.9% in Egypt (Gaafar et al, ); in Zebu cows and its crosses, and in Murrah buffalo, the incidence of RFM is 26, 16, and 13%, respectively (Kumari et al, ). RFM results in considerable economic loss due to decreased milk production (Dubuc et al, ; Kumari et al, ); longer interval to first estrus and breeding; increased number of services per conception; lower conception rate and higher incidence of metritis (LeBlanc, ; Gaafar et al, ); and increased culling rate (Beagley et al, ). Cows with RFM or metritis produce 753 kg less milk per lactation, based on a 305‐day production period (Dubuc et al, ), which accounts for a ∼10% reduction in milk production—an estimated average loss of about £240 per RFM case (Esslemont and Peeler, ).…”
Section: Introductionmentioning
confidence: 99%
“…Cholesterol concentrations were significantly higher in the uterine fluid obtained from subclinical endometritis‐affected buffaloes as compared to normal buffaloes. Lower serum cholesterol has been shown to be associated with retention of foetal membranes (Kumari et al., ) and metritis (Patbandha et al., ) in cows. High cholesterol levels lead to cholesterol accumulation in macrophages and other immune cells, which promotes inflammatory responses, including augmentation of Toll‐like receptor signalling.…”
Section: Discussionmentioning
confidence: 99%
“…Losses incurred due to decreased milk production from RFM result in significant economic drainage to the dairy industry (Dubuc et al, 2011;. It has been reported that in RFM affected buffaloes milk yield decreased by 239 kg in a single lactation (Kumari et al, 2016). Delayed uterine involution, resumption of ovarian activity, increase in days open, reduction in pregnancy rate McDougall (2001), increase in removal of affected animals Beagley et al (2010), increased services per conception Holt et al (1989) and reduction in conception rate and increase in frequency of metritis Gaafar et al (2010) are the major negative sequelae of RFM.…”
Section: Sequelae and Economic Importancementioning
confidence: 99%